Gryphon in glory - Norton, Andre (New York : Ballantine Books, 1984)
Unrest fills the Dales as Joisan sets out from her refuge to seek out her husband, Kerovan, journeying on a secret mission in the Waste where the evil powers of the Dark threaten on every hand. Companion to the earlier book, The Crystal Gryphon.
"A Del Rey book."
Keywords: Fantasy